An unusual cause of ascites and pleural effusion in an elderly woman: Sarcoidosis presenting with parailiac lymph node involvement - Sahin, Abdurrahman; Artas, Hakan; Artas, Gokhan (Aves, 2020)
[Abstract Not Available]